2009
DOI: 10.1002/hyp.7316
|View full text |Cite
|
Sign up to set email alerts
|

High chloride concentrations in the soil and groundwater under an oak hedge in the West of France: an indicator of evapotranspiration and water movement

Abstract: Abstract:Chloride is a major anion in soil water and its concentration rises essentially as a function of evapotranspiration. Compared to herbaceous vegetation, high transpiration rates are measured for isolated trees, shelterbelts or hedgerows. This article deals with the influence of a tree hedge on the soil and groundwater Cl concentrations and the possibility of using Cl as an indicator of transpiration and water movements near the tree rows. Cl concentrations were measured over 1 year at different depths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…This hypothesis can be verified using direct methods to evaluate transpiration such as sap flow measurements. The importance of the evapotranspiration in hedgerow system in temperate climate has been recently confirmed as revealed by the large increase of chloride in the soil below hedges, because of residual accumulation following tree root water extraction (Grimaldi et al , 2009).…”
Section: Discussionmentioning
confidence: 92%
“…This hypothesis can be verified using direct methods to evaluate transpiration such as sap flow measurements. The importance of the evapotranspiration in hedgerow system in temperate climate has been recently confirmed as revealed by the large increase of chloride in the soil below hedges, because of residual accumulation following tree root water extraction (Grimaldi et al , 2009).…”
Section: Discussionmentioning
confidence: 92%
“…These values fit within a continuum of steadily increasing solute concentrations from 1985-1989to 2001to 2010. Chloride is an especially effective and widely used conservative tracer because it is biologically inactive and its catchment inputs are largely restricted to atmospheric deposition, thereby limiting the possible sources responsible for concentration increases (Hayashi et al, 1998;Grimaldi et al, 2009). Finally, the present-day pattern, whereby shrinking lakes have higher solute concentrations than stable and expanding lakes, was weak but not entirely absent in the 1980s, especially for Mg and Na.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that adsorption-like processes in soil organic matter, hydrology and microbial soil activity influence stream chloride concentration. Other studies reported local storage of chloride in soils, for instance under hedges due to higher evapotranspiration (Grimaldi et al, 2009), and in groundwater (Rouxel et al, 2011). Imbalances of the chloride budgets are also reported in catchments where land-use changes occurred (Guan et al, 2010;Oda et al, 2009).…”
Section: Annual Patternsmentioning
confidence: 91%